From Black Bile to the Bipolar Spectrum: A Historical Review of the Bipolar Affective Disorder Concept - Justin Thomas; Ian Grey (Archives of Depression and Anxiety - Peertechz Publications, 2016)
The terms melancholia and mania have their etymologies in classical Greek. Melancholia is derived from  'melas' (black) and 'chole' (bile), highlighting the term's origins in pre-Hippocratic humoral  theories  [ 1 ].  Where depression/melancholia  was  viewed as an excess of black bile, the humoral perspective saw mania as arising from an excess of yellow bile [ 2 ], or a mixture of excessive black and yellow bile [ 3 ]. The exact origins of the term mania however, are not  as clear-cut as those outlined for melancholia. The Roman physician, Caelius Aurelianus, proposes several  origins  for  the  word  mania, including  the  Greek  word 'ania', meaning to produce great mental anguish.  He also suggests  'manos', meaning  relaxed or loose, which would approximate to an excessive relaxing of the mind or soul [ 4 ]. There are at  least five other etymological candidates proposed by Aurelianus for the word mania and  the  confusion  surrounding  the exact etymology is attributed to its varied usage in the pre-Hippocratic poetry and mythologies [ 4 ].